Effect of effective microorganism on paddy growth performance / Afza Dini Adz-Zahra Arzahari - Arzahari, Afza Dini Adz-Zahra (Faculty of Plantation and Agrotechnology, 2019)
Rice is the staple food for Malaysia. Rice production in the country is insufficient to meet the demand of our population. In order to overcome the shortage, Malaysia had to import rice from other country like Thailand. To overcome the fertility problem of abandoned lands, inorganic fertilizers can be used together with EM. The effective microorganisms improve soil chemical properties, soil fertility and plant where they do activities of microorganisms in the soil. The effect of different rate of EM on growth performance of rice is based on Complete Randomized Design (CRD) an experiment has been carried out based on 4 replications. The objective of this study is to compare the effects of EM towards the plant height, tiller and yield and to determine the best rate of EM concentration and effect towards the rice. The variety of rice used is MR219 and the different rate of EM were applied in 3 different amount of concentration 1.1 x 109cfu, 3.3 x 109cfu, 5.5 x 109 cfu. Dilute solutions of effective microorganism (EM) had a beneficial effect on such as number of tiller, plant height and number of grain per panicle. The highest number of mean value of grain per panicle (115) was recorded in plant treated with 5.5x109 cfu concentration of Effective Microorganism (EM). From this study, the treatment of Effective Microorganism (EM) was proved in boosting a better performance of paddy crop.